264 Diagnostic algorithm for uterine sarcoma identification: a 1-year interim analysis of a monocentric prospective, observational cohort study. (18th September 2019) - Ciccarone, F; Pasciuto, T; Robba, E; Mascilini, F; Moro, F; Manfredi, R; Scambia, G; Romualdi, D; Testa, AC
Abstract : Objectives: Uterine sarcomas are rare malignant tumors arising from the mesenchymal tissues of the uterus including the endometrial stroma, uterine muscle and connective tissue. The diagnosis of uterine sarcomas is a challenge and no validated clinical or radiological criteria can accurately distinguish benign from malignant myometrial tumors. In particular, data on the ultrasound features of uterine sarcomas are scarce and they are mainly based on retrospective case series. Methods: This is a monocentric, prospective, observational cohort study. All patients with at least one myoma of 3 cm or more will be included in MYLUNAR study and will be assessed by Green Card criteria. If one of the Green Card criteria is present, a dedicated clinical and ultrasound paper form will be filled in to check the presence of the criteria described in the Orange Card. If at least two suspicious characteristics according to Orange Card criteria are present, Magnetic Resonance imaging will be performed and the patients will be submitted to surgery. Results: In this 1-year interim analysis, we analysed 816 patients who were selected by MYLUNAR study criteria. The ad-interim analysis is expected to be concluded in May 2019, and we will present the results at the meeting. Conclusions: The discrimination between benign and malignant myometrial lesions is clinically relevant to plan the optimal management (surgery, interventional procedures, or medical treatment) and to define the most appropriate surgical approach. By defining an accurate diagnostic algorithm in identifying patients with uterine sarcomas, MYLUNAR study may represent the guide line in the management of women with myometrial lesion.